Gamma-Band Auditory Steady-State Response as a Neurophysiological Marker for Excitation and Inhibition Balance: A Review for Understanding Schizophrenia and Other Neuropsychiatric Disorders. (July 2020) - Tada, Mariko; Kirihara, Kenji; Koshiyama, Daisuke; Fujioka, Mao; Usui, Kaori; Uka, Takanori; Komatsu, Misako; Kunii, Naoto; Araki, Tsuyoshi; Kasai, Kiyoto
Altered gamma oscillations have attracted considerable attention as an index of the excitation/inhibition (E/I) imbalance in schizophrenia and other neuropsychiatric disorders. The auditory steady-state response (ASSR) has been the most robust probe of abnormal gamma oscillatory dynamics in schizophrenia. Here, we review recent ASSR studies in patients with schizophrenia and other neuropsychiatric disorders. Preclinical ASSR research, which has contributed to the elucidation of the underlying pathophysiology of these diseases, is also discussed. The developmental trajectory of the ASSR has been explored and may show signs of the maturation and disruption of E/I balance in adolescence. Animal model studies have shown that synaptic interactions between parvalbumin-positive GABAergic interneurons and pyramidal neurons contribute to the regulation of E/I balance, which is related to the generation of gamma oscillation. Therefore, ASSR alteration may be a significant electrophysiological finding related to the E/I imbalance in neuropsychiatric disorders, which is a cross-disease feature and may reflect clinical staging. Future studies regarding ASSR generation, especially in nonhuman primate models, will advance our understanding of the brain circuit and the molecular mechanisms underlying neuropsychiatric disorders.